Composite negative electrode material and negative electrode and battery using same

By covering the conductive polymer prepared by bisthiophene aromatic compound on the negative electrode active material of the battery, the mechanical stress problems and insufficient conductivity caused by volume expansion and contraction of silicon materials in the battery are solved, and the energy density and cycling performance of the battery are improved.

CN119786560AActive Publication Date: 2025-04-08EVE ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411960461.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The volume of silicon material expands and contracts greatly during the charging and discharging of the battery, resulting in an increase in mechanical stress. After multiple cycles, the silicon particles break and powder become broken, causing the negative electrode to fail. At the same time, the contact between silicon and the conductive agent and the negative electrode binder is poor, affecting the electrode conductivity.

Method used

A composite negative electrode material is used, which includes an anode active material and a conductive polymer coated therein. The raw materials of the conductive polymer include a bisthiophene aromatic compound. The negative electrode active material is coated with a benzodithiophene compound to enhance its conductive and mechanical properties, inhibit expansion and improve the energy density and cycling properties of the battery.

Benefits of technology

By enhancing the conductivity and mechanical properties of the negative electrode active material, it improves its stability during the charging and discharging process, improves the energy density and rate performance of the battery, and at the same time extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786560A_ABST
    Figure CN119786560A_ABST
Patent Text Reader

Abstract

The invention provides a composite negative electrode material and a negative electrode and a battery using the same, the composite negative electrode material comprises a negative electrode active material and a conductive polymer coating the negative electrode active material, and the raw material for preparing the conductive polymer comprises a bithiophene aromatic compound; the chemical structural formula of the bithiophene aromatic compound is # imgabs0, wherein A is independently selected from at least one of H, a thiophene ring, a 2-trimethyltin thiophene ring and a thiazole ring; r1, R2, R3 and R4 are independently selected from at least one of H, halogen atoms, alkyl groups and alkyl tin groups; r5 and R6 are independently selected from at least one of H, halogen atoms and alkyl, or R5 and R6 and atoms connected with R5 and R6 form at least one of thiophene rings, thiazole rings and 2-trimethyltin thiophene rings. The negative electrode active material is coated with the benzodithiophene compound, so that the conductivity of the negative electrode active material can be enhanced, the mechanical property of the negative electrode active material can be enhanced, and the expansion of the negative electrode active material can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a composite negative electrode material and a negative electrode and a battery using the same. Background Art

[0002] With the development of science and technology, people are becoming more and more dependent on electronic devices, and the requirements for battery life are also getting higher and higher. For example, the frequency of use of smartphones is very high. If the battery capacity is small, it needs to be charged frequently, which brings inconvenience to users. Therefore, increasing the battery capacity can meet the user's demand for long-term use of electronic devices.

[0003] Since silicon is the second most abundant element in the earth's crust, second only to oxygen, and has a wide range of sources, this helps reduce the cost of batteries. The theoretical specific capacity of silicon is as high as 4200mAh / g, which is more than 10 times that of traditional graphite materials. This means that the use of silicon materials can significantly increase the energy density of batteries, thereby improving the battery's endurance. In addition, silicon has a low operating voltage, which can further increase the energy density of batteries.

[0004] Although silicon materials have broad application prospects in batteries, they also face some challenges. For example, the volume expansion and contraction of silicon during charging and discharging can reach 320% (graphite only 12%), which will produce large mechanical stress. After multiple cycles, silicon particles will break and pulverize, causing negative electrode failure. In addition, silicon has poor contact with conductive agents and negative electrode binders, resulting in poor overall conductivity of the electrode, affecting battery performance. Summary of the invention

[0005] In order to improve the electrochemical performance of a battery, the present invention provides a composite negative electrode material and a negative electrode and a battery using the same.

[0006] According to one aspect of the present application, a composite negative electrode material is provided, the composite negative electrode material comprising a negative electrode active material and a conductive polymer coating the negative electrode active material, the raw material for preparing the conductive polymer comprising a bithiophene aromatic compound; the chemical structural formula of the bithiophene aromatic compound is: Wherein, A is independently selected from at least one of H, thiophene ring, 2-trimethyltinthiophene ring, and thiazole ring; R 1 , R 2 , R 3 , R 4 , independently selected from at least one of H, a halogen atom, an alkyl group, and an alkyltin group; R 5 , R 6 is independently selected from at least one of H, a halogen atom, an alkyl group, or R 5 and R 6 Together with the atoms to which they are connected, they form at least one of a thiophene ring, a thiazole ring, and a 2-trimethyltinthiophene ring.

[0007] The present invention can not only enhance the conductivity of the negative electrode active material by coating the benzodithiophene compound on the negative electrode active material, but also enhance the mechanical properties of the negative electrode active material and inhibit its expansion. This is mainly because the benzodithiophene compound has a large conjugated plane structure, which is conducive to the transmission of electrons, thereby improving the energy density and rate performance of the battery. At the same time, the benzodithiophene compound has good rigidity and flexibility, which can enhance the mechanical properties of the negative electrode active material, thereby improving the cycle performance of the battery.

[0008] Preferably, the bithiophene aromatic compound comprises at least one of a first monomer and a second monomer; wherein the chemical structure of the first monomer is The chemical structure of the second monomer is R 1 , R 2 , R 3 , R 4 At least one of halogen atoms and alkyl groups is independently selected. The conductive polymer obtained by polymerizing the first monomer and the second monomer has both benzobithiadiazole and benzodithiophene, which have a larger conjugated planar structure, and can further improve the transmission of electrons, thereby further enhancing the rate performance of the battery.

[0009] Preferably, the number of carbon atoms in the alkyl group is ≥5.

[0010] Preferably, calculated according to the molar ratio, the first monomer: the second monomer = 1-4: 1-7.

[0011] Preferably, the molecular weight of the conductive polymer is 6,000-40,000.

[0012] Preferably, the raw material for preparing the conductive polymer further comprises a dibromothiophene compound, the structural formula of the dibromothiophene compound is Among them, R 7 , R 8 At least one of H, carboxyl and alkyl is independently selected. By introducing the dibromothiophene compound, hydrogen bonds can be formed between the conductive polymer and the negative electrode active material, which can further enhance the interface stability of the composite negative electrode material, thereby enhancing the cycle performance of the battery.

[0013] Preferably, the bithiophene aromatic compound comprises monomer I; wherein the chemical structure of monomer I is A is independently selected from at least one of H and thiophene ring; R 5 , R 6 Independently selected from at least one of H, halogen atoms, and alkyl groups. Furthermore, a symmetrical 2-trimethyltinthiophene ring is introduced into the bithiophene aromatic compound to further improve the conductive properties of the material.

[0014] Preferably, calculated by molar ratio, the bithiophene aromatic compound: dibromothiophene compound = 1:1-3.

[0015] Preferably, the molecular weight of the conductive polymer is 5,000-30,000.

[0016] Preferably, the preparation method of the conductive polymer comprises the following steps: S1. Under anhydrous and oxygen-free conditions, mixing a bithiophene aromatic compound, or a bithiophene aromatic compound and a dibromothiophene compound, with an organic solvent, then adding a catalyst, and reflux reacting at 70 to 125° C. for 6 to 24 hours to obtain a first solution; S2. Then filtering the first solution, washing the solid portion obtained by the filtering treatment with ether to obtain an ether washing liquid; S3. Mixing the ether washing liquid with the filtrate obtained in the above filtering step, adding a saturated potassium fluoride aqueous solution, and obtaining an organic layer after standing; S4. Transferring the organic layer, adding a saturated sodium chloride solution to the organic layer for washing, and then drying with anhydrous magnesium sulfate to obtain a crude product; S5. Purifying the crude product by neutral alumina column chromatography, wherein n-hexane is used as an eluent, to obtain a conductive polymer.

[0017] Preferably, the organic solvent is at least one of benzene, toluene, acetone and N,N-dimethylformamide (DMF).

[0018] Preferably, the catalyst comprises tetrakistriphenylphosphine palladium (Pd(PPh 3 ) 4 ), dichlorobis(triphenylphosphine)palladium (Pd(PPh 3 ) 2 Cl 2 ) at least one of.

[0019] Preferably, in the composite negative electrode material, D of the negative electrode active material is 50 The thickness of the conductive polymer is 3 to 10 μm, and the thickness of the conductive polymer is 5 to 80 nm.

[0020] Preferably, the negative electrode active material comprises a silicon material.

[0021] Preferably, the silicon material comprises silicon carbon.

[0022] Preferably, the thickness of the silicon layer in the silicon carbon is 1 nm to 10 nm.

[0023] Preferably, among the internal pores and external pores of silicon carbon, the proportion of mesopores is 45-88%, and the proportion of micropores is less than 60%, wherein the diameter of the mesopores is 3-45 nm, and the diameter of the micropores is 1-2 nm.

[0024] Preferably, in the negative electrode active material, the mass content of silicon element is 30% to 80%.

[0025] Preferably, the preparation of the composite negative electrode material includes the following steps: dissolving the conductive polymer in tetrahydrofuran (THF) solvent to prepare a solution with a mass fraction of 5 to 30%; adding the negative electrode active material to the above solution, stirring at 40 to 80° C. for 4 to 10 hours to obtain a mixed solution; and then spray drying the mixed liquid to obtain a composite negative electrode material.

[0026] Preferably, the operating parameters of the spray drying process are: inlet temperature is 100-200°C, and outlet temperature is 50-90°C.

[0027] The second aspect of the present invention provides a negative electrode, which includes the composite negative electrode material as described above.

[0028] According to a third aspect of the present invention, a battery is provided, comprising the negative electrode as described above.

[0029] Preferably, the battery includes an electrolyte, which includes 1-5% lithium bis(fluorosulfonyl)imide (LiFSI) and 5-10% methyl trifluoroethyl carbonate (FEMC) by weight. By adding the above electrolyte additives, the ion conductivity of the battery can be further improved. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0031] Example 1

[0032] 1. Preparation of composite negative electrode materials

[0033] (1) Preparation method of conductive polymer

[0034] S1. Under anhydrous and oxygen-free conditions, 1 mmol of 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-c:4,5-c']bis[1,2,5]thiadiazole (CAS No.: 1401018-41-4) and 1 mmol of (4,8-bis(4-chloro-5-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-b:4,5-b']dithiophene-2,6-diyl)bistrimethyltin (CAS No.: 2239295-69-1) were mixed with 25 mL of N,N-dimethylformamide (DMF), and then tetrakistriphenylphosphine palladium (Pd(PPh 3 ) 4), reflux reaction at 100° C. for 18 hours to obtain a first solution;

[0035] S2. The first solution is then filtered, and the solid portion obtained by the filtration is washed with ether to obtain an ether washing solution;

[0036] S3. The ether washing solution was mixed with the filtrate obtained in the above filtration step, a saturated aqueous solution of potassium fluoride was added, and the organic layer was obtained after standing;

[0037] S4. The organic layer was transferred and a saturated sodium chloride solution was added to the organic layer for washing, followed by drying over anhydrous magnesium sulfate to obtain a crude product;

[0038] S5. Purify the crude product using neutral alumina column chromatography with n-hexane as eluent to obtain a conductive polymer.

[0039] (2) Preparation method of composite negative electrode material

[0040] The conductive polymer was dissolved in tetrahydrofuran (THF) solvent to prepare a solution with a mass fraction of 20%; silicon carbon was added to the above solution and stirred at 60°C for 8 hours to obtain a mixed solution; the mixed liquid was then spray-dried to obtain a composite negative electrode material. The operating parameters of the spray drying process were: inlet temperature of 150°C, outlet temperature of 70°C; the obtained composite negative electrode material D 50 The thickness of the conductive polymer is 6 μm and 60 nm.

[0041] 2. Preparation of Lithium-ion Batteries

[0042] (1) Preparation of positive electrode sheet

[0043] The ternary material NCM811 (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) The positive electrode active material, binder PVDF (polyvinylidene fluoride), and conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:2:2 to obtain a positive electrode slurry, and then the positive electrode slurry is coated on an aluminum foil through a coating process, and a positive electrode sheet is obtained after drying and cold pressing processes.

[0044] (2) Preparation of negative electrode sheet

[0045] The composite negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 80:9:1:10 to obtain a negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on a copper foil through a coating process, and a negative electrode sheet is obtained after vacuum drying and cold pressing processes.

[0046] (3) Selection of electrolyte

[0047] EC:DMC:DEC:FEC=20:40:30:10,LiPF 6 1mol / L for preparing lithium-ion batteries.

[0048] (4) Selection of isolation membrane

[0049] Polyethylene (PE) and ceramics are selected as separators for lithium-ion batteries.

[0050] (5) Preparation of lithium-ion batteries

[0051] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0052] Example 2

[0053] This embodiment refers to the formula and method provided in Example 1 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 1 is that this embodiment replaces the raw materials used when preparing the composite negative electrode material. In addition to the above differences, the operation steps of preparing the composite negative electrode material and the negative electrode and a battery using the same in this embodiment are strictly consistent with those in Example 1. Specifically, the steps of preparing the composite negative electrode material in this embodiment are:

[0054] S1. Under anhydrous and oxygen-free conditions, 1 mmol of 2,5-dibromothiophene-3,4-dicarboxylic acid (CAS No.: 190723-12-7) and 1 mmol of 5,6-difluoro-4,7-bis(5-(trimethyltinyl)thiophen-2-yl)benzo[c][1,2,5]thiadiazole (CAS No.: 1421762-30-2) were mixed with 25 mL of benzene, followed by the addition of dichlorobis(triphenylphosphine)palladium (Pd(PPh 3 ) 2 Cl 2 ), reflux reaction at 110° C. for 18 hours to obtain a first solution;

[0055] The operation steps of S2 to S5 are strictly consistent with those of Example 1. 50 The thickness of the conductive polymer is 6 μm and 65 nm.

[0056] Example 3

[0057] This embodiment refers to the formula and method provided in Example 1 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 1 is that this embodiment uses 2,5-dibromothiophene-3,4-dicarboxylic acid (CAS No.: 190723-12-7) to replace 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophene-2-yl)benzo[1,2-c:4,5-c']bis[1,2,5]thiadiazole (CAS No.: 1401018-41-4) when preparing the composite negative electrode material. The operation steps for preparing the composite negative electrode material and the negative electrode and battery using the same in this embodiment are strictly consistent with those in Example 1. Specifically, the steps for preparing the composite negative electrode material in this embodiment are:

[0058] S1. Under anhydrous and oxygen-free conditions, 1 mmol of 2,5-dibromothiophene-3,4-dicarboxylic acid (CAS No.: 190723-12-7) and 1 mmol of (4,8-bis(4-chloro-5-(2-ethylhexyl)thiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene-2,6-diyl)bistrimethyltin (CAS No.: 2239295-69-1) were mixed with 25 mL of N,N-dimethylformamide (DMF), and then dichlorobis(triphenylphosphine)palladium (Pd(PPh 3 ) 2 Cl 2 ), reflux reaction at 100° C. for 18 hours to obtain a first solution;

[0059] The operation steps of S2 to S5 are strictly consistent with those of Example 1. 50 The thickness of the conductive polymer is 58 nm.

[0060] Example 4

[0061] This embodiment refers to the formula and method provided in Example 1 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 1 is that this embodiment uses 5,6-difluoro-4,7-bis(5-(trimethyltin)thiophene-2-yl)benzo[c][1,2,5]thiadiazole (CAS No.: 1421762-30-2) to replace (4,8-bis(4-chloro-5-(2-ethylhexyl)thiophene-2-yl)benzo[1,2-b:4,5-b']dithiophene-2,6-diyl)bistrimethyltin (CAS No.: 2239295-69-1) when preparing the composite negative electrode material. In addition to the above differences, the operation steps of preparing the composite negative electrode material and the negative electrode and battery using the same in this embodiment are strictly consistent with those in Example 1. Specifically, the steps of preparing the composite negative electrode material in this embodiment are as follows:

[0062] S1.S1. Under anhydrous and oxygen-free conditions, 1 mmol of 4,8-bis(5-bromo-4-(2-ethylhexyl)thiophen-2-yl)benzo[1,2-c:4,5-c']bis[1,2,5]thiadiazole (CAS No.: 1401018-41-4) and 1 mmol of 5,6-difluoro-4,7-bis(5-(trimethyltinyl)thiophen-2-yl)benzo[c][1,2,5]thiadiazole (CAS No.: 1421762-30-2) were mixed with 25 mL of N,N-dimethylformamide (DMF), and then tetrakistriphenylphosphine palladium (Pd(PPh 3 ) 4 ), reflux reaction at 100°C for 12 hours to obtain a first solution

[0063] The operation steps of S2 to S5 are strictly consistent with those of Example 1. 50 The thickness of the conductive polymer is 55 nm.

[0064] Example 5

[0065] This embodiment refers to the formula and method provided in Example 1 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 1 is that the composite negative electrode material D prepared in this embodiment is 50 The thickness of the composite negative electrode material is 12 μm (achieved by adjusting the operating parameters of the spray drying process). Except for the above differences, the operating steps of preparing the composite negative electrode material and the negative electrode and battery using the composite negative electrode material in this embodiment are strictly consistent with those in Example 1.

[0066] Example 6

[0067] This embodiment refers to the formula and method provided in Example 2 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 2 is that the composite negative electrode material D prepared in this embodiment is 50The thickness of the composite negative electrode material is 2 μm (achieved by adjusting the operating parameters of the spray drying process). Except for the above differences, the operating steps of preparing the composite negative electrode material and the negative electrode and battery using the composite negative electrode material in this embodiment are strictly consistent with those in Example 2.

[0068] Example 7

[0069] This embodiment refers to the formula and method provided in Example 2 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 2 is that the thickness of the conductive polymer of the composite negative electrode material prepared in this embodiment is 83nm (achieved by controlling the conductive polymer to dissolve in THF solvent and configuring it into a solution with a mass fraction of 25%). Except for the above differences, the operating steps for preparing the composite negative electrode material and the negative electrode and the battery using the same in this embodiment are strictly consistent with those in Example 2.

[0070] Example 8

[0071] This embodiment refers to the formula and method provided in Example 2 to prepare a composite negative electrode material and a negative electrode and a battery using the same. The difference from Example 2 is that the electrolyte used in this embodiment when preparing the battery introduces electrolyte additives LiFSI (with a mass content of 2%) and FEMC (with a mass content of 6%). Except for the above differences, the operating steps for preparing the composite negative electrode material and the negative electrode and the battery using the same in this embodiment are strictly consistent with those in Example 2.

[0072] Comparative Example 1

[0073] This comparative example prepares a negative electrode and a lithium-ion battery by referring to the formula and method provided in Example 1. The difference from Example 1 is that the negative electrode active material used in preparing the negative electrode in this comparative example is silicon carbon. Except for the above difference, the operating steps for preparing the composite negative electrode material and the negative electrode and lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 1.

[0074] Comparative Example 2

[0075] This comparative example refers to the formula and method provided in Example 1 to prepare a composite negative electrode material and a negative electrode and a lithium-ion battery using the same. The difference from Example 1 is that poly (3,4-ethylenedioxythiophene) is used instead of the bithiophene aromatic compound when preparing the composite negative electrode material. Except for the above difference, the operating steps for preparing the composite negative electrode material and a negative electrode and a lithium-ion battery using the same in this comparative example are strictly consistent with those in Example 1.

[0076] Test Case

[0077] 1. Test subjects

[0078] The composite negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2, and the negative electrodes and batteries using the same.

[0079] 2. Test Method

[0080] (1) First coulombic efficiency: At 25°C, charge the lithium-ion battery to 4.2V at a constant current and constant voltage rate of 0.33C, let it stand for 10 minutes, then discharge the lithium-ion battery to 2.5V at a constant current rate of 0.33C, let it stand for 10 minutes, and calculate the first coulombic efficiency of the lithium-ion battery. Calculate the first coulombic efficiency (first efficiency) according to the following formula:

[0081] First coulombic efficiency (%) = total capacity of lithium-ion battery discharged at 0.33C for the first time / total capacity of lithium-ion battery charged at 0.33C for the first time × 100%

[0082] (2) Capacity retention rate after 1200 cycles at room temperature at 1C / 1C: At 25°C, charge the lithium-ion battery to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and let it stand for 10 minutes. Then, discharge the lithium-ion battery to 2.5V at a constant current rate of 1C, and let it stand for 10 minutes. This is considered one charge and discharge cycle. Perform charge and discharge cycles of the lithium-ion battery for 1200 cycles according to the above method, and calculate the capacity retention rate after 1200 cycles of charge and discharge cycles of the lithium-ion battery at 1C / 1C. Calculate the capacity retention rate according to the following formula:

[0083] Capacity retention rate of lithium-ion battery after N cycles (%) = (discharge capacity of Nth cycle / first discharge capacity) × 100%, N is the number of cycles of lithium-ion battery

[0084] (3) 1C / 10C discharge capacity retention rate: At 25°C, the divided lithium-ion battery is charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C; let it stand for 10 minutes; then the lithium-ion battery is discharged to 2.5V at a constant current rate of 1C, and its discharge capacity Q1C is recorded as the initial discharge capacity; then the lithium-ion battery is charged to 4.2V at a constant current and constant voltage rate of 1C at 25°C, with a cut-off current of 0.05C; let it stand for 10 minutes; then the fully charged battery is discharged to 2.5V at a constant current rate of 10C, and its discharge capacity Q10C is recorded. The discharge capacity retention rate of the lithium-ion battery at a 1C / 10C rate is calculated according to the following formula:

[0085] Discharge capacity retention rate (%) = discharge capacity at 10C rate Q10C / discharge capacity at 1C rate Q1C × 100%

[0086] (4) Room temperature 6C rate performance - constant current charging ratio: At 25°C, the lithium-ion battery is discharged at a constant current rate of 1C to 2.5V, left to stand for 10 minutes, and then charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C, left to stand for 10 minutes, and the constant current charging capacity Q of the lithium-ion battery is recorded. 1 , constant current constant voltage charging total capacity Q 2 , calculate the 6C rate charging constant current charging ratio according to the following formula:

[0087] 6C rate charging constant current charging ratio = constant current charging capacity Q 1 / Constant current and constant voltage charging total capacity Q 2 ×100%

[0088] 3. Test results and analysis

[0089] The test results of this test case are shown in Table 1.

[0090] Among them, it can be seen from the test results of Examples 1 to 4 and Comparative Examples 1 to 2 that the electrochemical performance of lithium-ion batteries can be significantly enhanced by combining different dithiophene aromatic compounds or introducing dibromothiophene compounds. This is mainly because the benzodithiophene compound has a larger conjugated planar structure, which is conducive to the transmission of electrons, thereby improving the energy density and rate performance of the battery. Further, when the first monomer and the second monomer are polymerized to obtain a conductive polymer having both benzodithiadiazole and benzodithiophene, the two have a larger conjugated planar structure, which can further improve the transmission of electrons, thereby further enhancing the rate performance of the battery. Further, by introducing dibromothiophene compounds, hydrogen bonds can be formed between the conductive polymer and the negative electrode active material, which can further enhance the interfacial stability of the composite negative electrode material, thereby enhancing the cycle performance of the battery.

[0091] On the other hand, the data of Examples 1 and 5-6 can prove that the D of the composite negative electrode material 50 It will affect the cycle performance and rate performance of the battery. This may be because the D 50 It will affect the example transport performance of the battery; the data of Example 1 and Example 7 can illustrate that by regulating the thickness of the conductive polymer in the composite negative electrode material, it is helpful to enhance the interface stability of the composite negative electrode material, thereby enhancing the overall electrochemical performance of the battery.

[0092] In addition, the data of Example 8 proves that the ionic conductivity of the battery can be further improved by introducing lithium bis(fluorosulfonyl)imide and methyl trifluoroethyl carbonate (FEMC).

[0093] Table 1. Test results of this test case

[0094]

[0095] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A composite negative electrode material, characterized in that: The composite negative electrode material includes a negative electrode active material and a conductive polymer coating the negative electrode active material. The raw material for preparing the conductive polymer includes a dithiophene aromatic compound. The chemical structure of the dithiophene aromatic compound is: Wherein, A is independently selected from at least one of H, a thiophene ring, a 2-trimethyltinthiophene ring, and a thiazole ring; R1, R2, R3, and R4 are independently selected from at least one of H, a halogen atom, an alkyl group, and an alkyltin group; R5 and R6 are independently selected from at least one of H, a halogen atom, and an alkyl group, or R5 and R6 and the atoms to which they are connected form at least one of a thiophene ring, a thiazole ring, and a 2-trimethyltinthiophene ring.

2. The composite negative electrode material according to claim 1, characterized in that: The bithiophene aromatic compound includes at least one of a first monomer and a second monomer; Wherein, the chemical structure of the first monomer is The chemical structure of the second monomer is The R1, R2, R3 and R4 are independently selected from at least one of a halogen atom and an alkyl group.

3. The composite negative electrode material according to claim 2, characterized in that: The number of carbon atoms in the alkyl group is ≥5.

4. The composite negative electrode material according to claim 2, characterized in that: The molecular weight of the conductive polymer is 6,000-40,000.

5. The composite negative electrode material according to claim 1, characterized in that: The raw materials for preparing the conductive polymer also include a dibromothiophene compound, and the structural formula of the dibromothiophene compound is Wherein, R7 and R8 are independently selected from at least one of H, carboxyl and alkyl.

6. The composite negative electrode material according to claim 5, characterized in that: The bithiophene aromatic compound comprises monomer I; Wherein, the chemical structure of the monomer I is The A is independently selected from at least one of H and a thiophene ring; the R5 and R6 are independently selected from at least one of H, a halogen atom, and an alkyl group.

7. The composite negative electrode material according to claim 6, characterized in that: The molecular weight of the conductive polymer is 5000-30000.

8. The composite negative electrode material according to any one of claims 1 to 7, characterized in that: In the composite negative electrode material, the D of the negative electrode active material 50 The conductive polymer has a thickness of 3 to 10 μm and a thickness of 5 to 80 nm.

9. A negative electrode, characterized in that The negative electrode comprises the composite negative electrode material according to any one of claims 1 to 8.

10. A battery, characterized in that: The battery comprises the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Modified electrode material, preparation method thereof, and lithium-ion battery

    CN110854363A

  • Conjugated polymer based on benzodithiophene and thienopyrazine, preparation method and uses thereof

    EP2586810A1

  • Positive electrode active material for electrochemical device, positive electrode for electrochemical device, electrochemical device, and method for manufacturing positive electrode active material for electrochemical device

    US20180323432A1

  • Method of synthesis for organic semiconducting polymers

    US20210066606A1

  • Method and system for functional conductive polymer initiated cathode electrolyte interface for silicon anode-based lithium ion batteries

    US20210336268A1